The Perilous Journey of the Donner Party - Calabro, Marian (New York Clarion Books, 1999)
Uses material from letters and diaries written by survivors of the Donner Party to relate the experiences of that ill-fated group as they endured horrific circumstances on their way to California.
Keywords: Donner Party; Overland journeys to the Pacific; Survival